A home-based exercise intervention for caregivers of persons with dementia: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Chan, Wai; Lautenschlager, Nicola; Dow, Briony; Ma, Suk; Wong, Corine; Lam, Linda
Abstract Background Family members, who provide the majority of care for persons with dementia, are especially vulnerable to developing depression. Interventions targeting their depressive symptoms have been proposed but their efficacies vary considerably. It has been suggested that interventions carried out in the home setting and involving both caregivers and care recipients are more efficacious. This study aims to compare the efficacy of a home-based structured exercise programme involving both persons with dementia and their caregivers with nonexercise social contact control in treating depression among caregivers. Methods/design This is a parallel-group, assessor-blind, randomised controlled trial. A total of 136 caregiver-care-recipient dyads (i.e. 272 participants in total) will be recruited and randomly allocated to either a home-based structured exercise (sitting Tai Chi) group or a social contact control group. The trial comprises a 3-month intervention phase followed by an extended observation phase of another 3 months. All participants will be assessed at baseline, 6th week, 12th week and 24th week. The primary outcome will be the reduction in depression among caregivers as measured by the Hamilton Rating Scale for Depression. The secondary outcomes will be burden, quality of life, cognitive performance and balance ability of the caregivers, as well as the neuropsychiatric symptoms, cognitive function, balance and functional abilities of the persons with dementia. We will also examine whether the brain-derived neurotrophic factor gene modulates mood changes in response to exercise. Discussion The findings offer a potential avenue of intervention by providing a low-cost, safe and effective treatment for depression among dementia caregivers, which may in turn also benefit the care recipients. Trial registration ClinicalTrials.gov Identifier:NCT02132039, registered on 28 April 2014.